The Impact of a Deep Learning Approach on Students’ Science Process Skills and Learning Outcomes in Biology - Alexander Lado Wungubelen; Nurhayati B.; Firdaus Daud; Alimuddin Ali; Ismail (PT. Global Research Collaboration, 2026)
Despite the growing emphasis on student-centered learning in science education, many biology classrooms continue to rely on teacher-centered instruction, resulting in limited development of students’ science process skills and learning outcomes. This study aimed to investigate the effect of the Deep Learning approach on science process skills and biology learning outcomes among Grade XI students at SMA Negeri 1 Adonara Barat. A quasi-experimental study employing a nonequivalent control group design was conducted with 70 students selected through purposive sampling. Thirty-five students were assigned to the experimental group and 35 students to the control group. Data were collected using a science process skills essay test and a biology achievement multiple-choice test and were analyzed using descriptive and inferential statistics. The results showed that students taught through the Deep Learning approach achieved higher science process skills than those receiving conventional instruction, as reflected by a high N-gain score (0.70), 89% classical mastery, and a significant difference between groups (p = 0.001). The experimental group also demonstrated superior biology learning outcomes with an N-gain score of 0.65, 83% classical mastery, and a significant difference compared with the control group (p = 0.000). These findings suggest that meaningful, mindful, and joyful learning experiences enhance scientific inquiry skills and conceptual understanding. Furthermore, improvements in science process skills were accompanied by better academic achievement, indicating a close relationship between scientific practices and learning outcomes. Therefore, the Deep Learning approach is an effective pedagogical strategy for improving both science process skills and biology learning outcomes in secondary education.